Highly Efficient Labeling of Human Lung Cancer Cells Using Cationic Poly-l-lysine-Assisted Magnetic Iron Oxide Nanoparticles - Wang, Xueqin; Zhang, Huiru; Jing, Hongjuan; Cui, Liuqing (Nano-Micro Letters, 2015)
Cell labeling with magnetic iron oxide nanoparticles (IONPs) is increasingly a routine approach in the cell-based cancer treatment. However, cell labeling with magnetic IONPs and their leading effects on the biological properties of human lung carcinoma cells remain scarcely reported. Therefore, in the present study the magnetic γ-Fe2O3 nanoparticles (MNPs) were firstly synthesized and surface-modified with cationic poly-l-lysine (PLL) to construct the PLL-MNPs, which were then used to magnetically label human A549 lung cancer cells. Cell viability and proliferation were evaluated with propidium iodide/fluorescein diacetate double staining and standard 3-(4,5-dimethylthiazol-2-diphenyl-tetrazolium) bromide assay, and the cytoskeleton was immunocytochemically stained. The cell cycle of the PLL-MNP-labeled A549 lung cancer cells was analyzed using flow cytometry. Apoptotic cells were fluorescently analyzed with nuclear-specific staining after the PLL-MNP labeling. The results showed that the constructed PLL-MNPs efficiently magnetically labeled A549 lung cancer cells and that, at low concentrations, labeling did not affect cellular viability, proliferation capability, cell cycle, and apoptosis. Furthermore, the cytoskeleton in the treated cells was detected intact in comparison with the untreated counterparts. However, the results also showed that at high concentration (400 µg mL−1), the PLL-MNPs would slightly impair cell viability, proliferation, cell cycle, and apoptosis and disrupt the cytoskeleton in the treated A549 lung cancer cells. Therefore, the present results indicated that the PLL-MNPs at adequate concentrations can be efficiently used for labeling A549 lung cancer cells and could be considered as a feasible approach for magnetic targeted anti-cancer drug/gene delivery, targeted diagnosis, and therapy in lung cancer treatment.